2007
DOI: 10.1080/10623320701421644
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cocaine Induces Endothelin-1–Dependent Constriction of Rabbit Basilar Artery

Abstract: It has been postulated that ischemic stroke due to acute cocaine usage involves constriction of the cerebral vasculature. However, the mechanism underlying the constriction remains unclear. This study tested whether cocaine constriction was mediated via endothelin-1. Cocaine suffusion induced maintained constriction in the rabbit basilar artery in situ. The constriction was relaxed by PD145065, an endothelin A and B receptor antagonist. These results support the hypothesis that constriction of the cerebral vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In this regard, we demonstrated that ET receptor antagonist inhibited cocaine constriction in rabbit basilar artery in situ [9]. Consistent with the dependency of cocaine constriction on ET-1 release [9] are the findings of increased ET-1 release from cultured endothelial cells following 100 µmol/l cocaine for 3 h [10].…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…In this regard, we demonstrated that ET receptor antagonist inhibited cocaine constriction in rabbit basilar artery in situ [9]. Consistent with the dependency of cocaine constriction on ET-1 release [9] are the findings of increased ET-1 release from cultured endothelial cells following 100 µmol/l cocaine for 3 h [10].…”
Section: Introductionsupporting
confidence: 61%
“…While species differences may underlie this difference, it should also be considered that the lower contractile efficacy of cocaine in the rabbit basilar artery [9] as compared to the basilar artery in the rat (present results) may play a role. In any case, the present findings point to the varied contractile mechanisms utilized by cocaine to elicit constriction in cerebral and peripheral vessels.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations